Hume's Second Thoughts About Belief - Michael Jacovides (Journal of Modern Philosophy)
In the Appendix to the Treatise, Hume retracts his claim that perceptions with the same object only vary with respect to vivacity. In material in the appendix that he tells his reader to insert in Book 1, he explains his reasons: the vivacity connected to belief is different in kind from that from the vivacity connected to poetry. Poetry can be more vivid, in its way, than belief. Since Hume’s main arguments for the thesis that beliefs are vivid ideas in the main body of the Treatise depend on the assumption that ideas with the same object only vary in vivacity, he owes us new arguments from his claim. He provides various arguments for a slightly revised thesis that belief is a sort of vivid idea at the beginning of the appendix. Three of these arguments, an argument from introspection, an argument from the involuntariness of belief, and an appeal to the explanatory power of his account are preserved in the first Enquiry.